Association of Crab Species with the Mangrove Ecosystem in Gili Sulat East Lombok - Putri, Devi Karisna; Al Idrus, Agil; Syukur, Abdul; Mahrus, Mahrus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The mangrove ecosystem is inhabited by various macroinvertebrates, such as brachyuran crabs, hermit crabs, gastropods, and bivalves. The mangrove ecosystem is a primary habitat for crabs to grow and develop, and it serves as a nursery ground for young organisms before they reach adulthood. This research was conducted from September 2023 to June 2024 in Gili Sulat, East Lombok. The aim of this study is to determine the diversity of crabs in Gili Sulat and their association with mangrove species. The method used in this research is purposive sampling, taking into account the density of mangroves.The study found 12 mangrove species: Rhizophora mucronata, Rhizophora stylosa, Rhizophora apiculata, Ceriops tagal, Excoecaria agallocha, Bruguiera gymnorrhiza, Pemphis acidula, Avicennia marina, Lumnitzera racemosa, Xylocarpus rumphii, Cordia subcordata, and Osbornia octodonta. The mangrove density at station 1 was 1800 ind/ha, at station 2 was 1222 ind/ha, and at station 3 was 2411 ind/ha. The crabs found included 3 species: Baptozius vinosus, Notonyx sp, and Portunus pelagicus. The abundance of crabs at station 1 was 55.6 ind/ha, at station 2 was 33.3 ind/ha, and at station 3 was 66.7 ind/ha. The correlation between mangrove density and crab abundance had a coefficient of determination of 91.6%, indicating that mangrove density can significantly influence crab abundance. There is one species of crab that has a positive association with one species of mangrove, namely the crab species Baptozius vinosus and the mangrove species Rhizophora mucronata.